A experiência de ser filho(a) adolescente em famílias monoparentais femininas - Alves, Vanessa Antunes (2023)
The family represents a social group that has a direct influence on people's lives. In contemporary society, defining a concept of family is not easy, because, besides the existence of several family configurations, the subjects' conception of themselves must and should be respected. One of the possible family configurations concerns the one in which there is only one parent (father or mother) with the children, this is known as single-parent family. In the present study, the focus will be placed on this family configuration with adolescent children. Adolescence is a cultural, individual and historical phenomenon. Although it can be lived as a period of conflict and turbulence for many, there are others who go through this phase without presenting major problems and significant difficulties. Concerning single parenthood with the presence of teenage children, there is a certain lack of studies and discussions about these families and their particularities. The present study refers to a descriptive-exploratory and qualitative research, which aimed at understanding the experience of being a teenager in singleparent female families. Ten adolescent sons or daughters of single parent female families, aged 15 to 20 years old, who lived in a city in the interior of Rio Grande do Sul, participated in the study. The data were collected through a Sociodemographic Data Sheet and an Interview about the experience of being an adolescent son/daughter in a single parent female family, which were analyzed through Content Analysis. The results were organized and discussed through two articles: “The female single-parent family from the perspective of adolescent children”; and “Adolescence and the relationship with the mother in single-parenthood: Perception of adolescent children”. The adolescents perceived themselves as very important to their families, just as their mothers were. They occupied a structuring and central position in their lives and in the lives of their families, and there was an affective dependence on them, as a constantly present, active and protective figure in their lives. It is conjectured that for these adolescents there may be greater difficulties in experiencing adolescence because they have to get involved in family aspects, such as serving as social support to their mothers and taking on roles with greater responsibilities. The participants indicated an equal division of tasks at home, although there was still a predominance of the mother figure in some specific tasks. It is considered relevant to carry out new studies, for this concerns a specific reality, besides a particular moment in the lives of the participants, and the life cycle of their families.